Society-Based Hospital System Improvement: Model Finding with Technology Perspective - Yustim, Benny; Violina, Sriyani; Sinaga, Ardiles (International Journal of Psychosocial Rehabilitation, 2020)
Health problems faced by people in developing countries, especially pregnant women, have their own dynamics. The government as the party that has the authority in terms of alleviating problems related to the future of this nation is certainly always trying to make various strategic steps in anticipating existing problems with various policies. One of the policies carried out by the Cirebon local government related to issues related to the high maternal mortality rate, one of which was to initiate a society-based hospital policy. The implementation of the policy is expected to be accelerated with appropriate and targeted technology. The selection of appropriate and targeted technology in accordance with business processes developed from existing policies is expected to solve problems better.